Ultrasonic waves in densified suspensions - Kowalski, S.; Sikorski, M. (Archives of Acoustics, 2004)
A theory of propagation of ultrasonic waves in sediments is developed. The formulae for the phase velocity and the attenuation coefficient are determined as functions of wave frequency and the mass fraction of the solid phase. These formulae can be used, after suitable calibration, for determination of the solid mass fraction or the water content in densified suspensions. These structure parameters can be determined by measuring the transition time of ultrasonic wave through a given distance of sediment. The phase velocity dispersion curves and the attenuation coefficients determined theoretically and experimentally are plotted as functions of the solid mass fraction for sediment. Key words: ultrasounds, sediment, wave propagation, phase velocity, attenuation coefficient.